Emission characteristics of gadolinium ions in a water Cherenkov detector. (28th November 2022) - Iwata, Y; Sekiya, H; Ito, C
Abstract: To observe supernova relic neutrino events, 13 tons of gadolinium sulfate octahydrate (Gd2 (SO4 )3 ·8H2 O), corresponding to 0.01% Gd solution, was dissolved in the Super-Kamiokande water Cherenkov detector in 2020. The aim is to improve the detection efficiency of neutrons from inverse β decay involving electron antineutrinos. However, Gd 3+ ions can be excited by the Cherenkov light from cosmic muons, and the subsequent emission at 312 nm is a possible background (BG) source for Cherenkov signal detection. In this work, we constructed an experimental setup based on time-resolved laser-induced luminescence spectroscopy to investigate the emission characteristics of Gd 3+ ions in water. The excitation laser wavelength was tuned in the range of 245–255 nm, and large resonant peaks were observed at 246.2 nm and 252.3 nm with measured emission lifetimes of around 3 ms. Good linearity was observed between Gd concentration and emission intensity for these two wavelengths, indicating that our setup is useful for remote monitoring of Gd concentration. According to the simulation results using our spectroscopic data and reference values, the Gd 3+ emission BG rate from cosmic muons is expected to be 10 −1 counts/μs or less, which seems small but not negligible.